Evaluation of intracellular calcium in golden retriever muscular dystrophy - Miyazato, Ligia G. [UNESP] (2011)
The present study had the objective of evaluating calcium accumulations in muscle fibers and their correlation with the canine muscular dystrophy. After the deaths of the animals (13 dystrophic and 3 non-dystrophic), samples of the skeletal muscles were collected. The material was stained with hematoxylin-eosin, Gomori's modified trichrome and alizarin red S technique (pH 4.3). The histopathological changes were analyzed and the proportions of calcium-positive (CPF) and negative muscle fibers were evaluated. Histopathological changes such as muscle fiber diameter changes, necrosis, hyalinization, presence of inflammatory infiltrate and fatty atrophy were identified in all the dystrophic muscles. Statistically significant differences in numbers of CPF between dystrophic muscles and non-dystrophics were observed for the masseter (6%), brachial biceps (5%) and triceps, sartorius and femoral biceps (4%) muscles. The identifying calcium is of interest as a parameter for helping in diagnostic screening.